PENGARUH KOMUNIKASI, PENGAWASAN DAN DISIPLIN TERHADAP PENINGKATAN PRODUKTIVITAS KERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA RANTAU PRAPAT - Laura Junita Sinuraya; Syahrina Effendi; Nany Haryani Harahap; Mery Chistina Batubara; Muhammad Mahiddin (Universitas Islam Islam Sumatera Utara, 2021)
The problems in this research are: How is the influence of communication, supervision and discipline partially and concurrently on the productivity of employees work in the Kantor Pelayanan Pajak Pratama Rantau Prapat? Research objectives: To determine the effect of communication, supervision and discipline partially and simultaneously on the productivity of employees work in the Kantor Pelayanan Pajak Pratama Rantau Prapat. The hypothesis proposed is: There is a significant effect of communication, supervision and discipline partially and jointly on the productivity of employees work in the Kantor Pelayanan Pajak Pratama Rantau Prapat. The study was conducted at the Kantor Pelayanan Pajak Pratama Rantau Prapat Jalan Ahmad Yani Rantau Prapat 21415, with a population of 124 people, and a study sample of 95 people. Based on the analysis results obtained communication have a positive and significant effect on the productivity of employees work of the Kantor Pelayanan Pajak Pratama Rantau Prapat, this is supported by the results of t count analysis t-table (3,162 1,661) at n = 95 at 95% significance level. Supervision has a positif and significant effect on the productivity of employees work of the Primary Tax Service Office of Rantau Prapat, this is supported by an analysis of t count t-table (2,613 1,661) at n = 95 at 95% significance level. Discipline has a positif and significant effect on the productivity of employees work of the Kantor Pelayanan Pajak Pratama Rantau Prapat, this is supported by an analysis of t count -table (5,190 1,661) at n = 95 with a significant level of 95%. Value of F-count F table (37,813 2,70) This states that together (multiple) there are positive and significant effects of communication, supervision and discipline on the productivity of employees work of employees of the Kantor Pelayanan Pajak Pratama Rantau Prapat . Thus the hypothesis proposed is accepted by the truth